Identification and quantitation of the rice aroma compound, 2-acetyl-1-pyrroline, in bread flowers (Vallaris glabra Ktze) - Wongpornchai S. (2014)
The aroma impact compound, 2-acetyl-1-pyrroline (2AP), has been identified for the first time in headspace of fresh bread flowers (Vallaris glabra Ktze) in which volatile components were extracted by solid-phase microextraction (SPME) at room temperature prior to analysis by gas chromatography-mass spectrometry. A total of 50 volatiles were detected. Among these, 23 volatiles were identified, predominantly in a group of terpenes. More volatiles were found in the extract of fresh bread flowers obtained by continuous steam distillation and solvent extraction (SDS). Of the 40 volatiles identified, the additional components were mainly straight-chain saturated hydrocarbons. 2AP was found in the extracts obtained by both SPME (0.37%) and SDS (2.71% relative proportion). Quantitative analyses of 2AP in bread flowers and other plant materials were performed by solvent extraction employing acidic solutions and capillary GC with flame ionization detection. The highest concentration of 2AP was found in dried flowers of V. glabra at 26.1 mg/kg. By comparison with other plant sources, fresh leaves of Pandanus amaryllifolius Roxb contain 2AP at 10.3 mg/kg and Thai fragrant rice, Khao Dawk Mali 105, at 3.0 mg/kg.